Sosialisasi Literasi Positif Melalui Media Sosial “Steemit” pada Santri Dayah Darul Muta’llimin Aceh Barat - Putri Maulina (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Positive literacy is the ability of individuals in languages such as writing, reading, or speaking well that has a positive impact. In the era of development of communication and information technology, one of the media that can increase the ability to titrate is social media. Steemit is a weblog type social media that has been popular since 2017. The aim of this service is to be able to socialize the concept of positive literacy by using the new Steemit social media on Santri Dayah Darul Muta’allimin, West Aceh. Service methods used are lectures and training. The results obtained in this service are strengthening of students with an emphasis on understanding the concept of positive literacy, techniques for registering and using social media Steemit, as well as understanding about building networks and getting rewarded through literacy on Steemit social media.